Eric Calderwood, “On Earth or in Poems: The Many Lives of al-Andalus”, Harvard University Press, 2023 - Cardoso, Elsa (Ex Novo: Journal of Archaeology, 2025)
In this book, Eric Calderwood, Professor of Comparative Literature, explores the diverse uses of al-Andalus in contemporary culture. The book encompasses literature, cinema, television, music, tourism, and political discourse, in Arabic, Spanish, French, and English. Calderwood takes a great research opportunity focusing on Arab and Muslim visions, usually dismissed in contemporary perspectives, to address nostalgic views of al-Andalus. This innovative approach is one of the highlights of the book, as al-Andalus can be either manipulated as a historical gap by the Catholic-nationalist discourse on the Reconquista or pictured as a model society in the framework of Convivencia theories.